Polaritonic states of matter in a rotating cavity - Cederbaum, Lorenz S. (The journal of physical chemistry letters, 2021)
The interaction of quantum light with matter like that inside a cavity is known to give rise to mixed light-matter states called polaritons. We discuss the impact of rotation of the cavity on the polaritons. It is shown that the number of polaritons increases because of this rotation. The structure of the original polaritons is modified, and new ones are induced by the rotation that strongly depend on the angular velocity and the choice of axis of rotation. In molecules the rotation can change the number of light-induced conical intersections and their dimensionality and hence strongly impact their quantum dynamics. General consequences are discussed.
Gesehen am 05.08.2021